Soil structure interaction analysis of toe kick-out failure - Tan, Paul Xiu Yi (2016)
Traditional methods of calculating toe kick-out of a braced retaining wall assume the wall deflects uniformly and fully mobilised earth pressures acting on the wall creating driving and resisting moments. In this project, a study of the differences between using the Finite Element Method (FEM) and conventional analysis on Toe Kick-Out failure was carried out. The results show that the lateral earth pressure acting on the braced excavation does not follow the simple Active and Passive pressures states. Several factors such as the Arching effect, Apparent Earth Pressures, Fixed Earth support pressures and Overlapping Passive Earth Pressures causes the Toe Kick-Out moments to be different from the conventional analysis results. When the model parameters were varied, the results showed that stiffer walls yield higher net moments due to rigid wall deflections which reduces the arching effect. Wider excavations led to reduced overlapping passive earth pressures, leading to greater deflections of the walls and increasing arching effect. Other factors contrary to the conventional analysis were found, such as point of rotation of the wall being in between the 1st and 2nd strut and the pressures obtained by FEM were not at the limit equilibrium but at moblized resistance states. Furthermore, the length of wall is also an amplifying factor leading to where changes of pressures farther away from the hinge had the most effect.